HUBUNGAN PRAKTIK PEMBERIAN ASI EKSKLUSIF DAN MP-ASI DENGAN KEJADIAN STUNTING DI PESISIR SUNGAI MUSI PALEMBANG - Sari Bema Ramdika; Nur Alam Fajar; Rostika Flora; Amrina Rosyada (JPK, 2025)
Abstract: Stunting is a condition of impaired growth in children resulting from chronic nutritional deficiencies, with long-term consequences on cognitive development, immune function, and future productivity. Inappropriate practices of exclusive breastfeeding and complementary feeding (MP-ASI), often influenced by low maternal knowledge and attitude, have been identified as major risk factors for stunting. This study aims to analyze the relationship between exclusive breastfeeding practices, maternal knowledge and attitudes related to MP-ASI, and the incidence of stunting among children under five in Palembang City. A cross-sectional study design was employed using a quantitative approach. Data were collected from 196 mothers with children aged 6–59 months across four sub-districts in Palembang City through multistage random sampling. Validated questionnaires were used as research instruments, and data were analyzed using the chi-square test. No significant association was found between knowledge (p=0.265) and attitude (p=0.652) regarding MP-ASI and stunting incidence. However, children of mothers with poor knowledge had a 2.175 times higher risk of stunting. Exclusive breastfeeding practices also showed no significant association with stunting (p=0.915), although children who were not exclusively breastfed had a 1.097 times higher risk of experiencing stunting. Although not statistically significant, low maternal knowledge on complementary feeding and lack of exclusive breastfeeding may increase the risk of stunting. Educational interventions promoting appropriate infant feeding practices are essential to reduce stunting prevalence in Palembang City.